Quantitative Structural Organization of Bulk Apical Membrane Traffic in Pollen Tubes - Grebnev, Gleb; Cvitkovic, Mislav; Fritz, Carolin; Cai, Giampiero; Smith, Ana-Suncana; Kost, Benedikt (Plant Physiology, 2020)
Pollen tube tip growth depends on balancing secretion of cell wall material with endocytic recycling of excess material incorporated into the plasma membrane (PM). The classical model of tip growth, which predicts bulk secretion, occurs apically, and is compensated by subapical endocytosis, has been challenged in recent years. Many signaling proteins and lipids with important functions in the regulation of membrane traffic underlying tip growth associate with distinct regions of the pollen tube PM, and understanding the mechanisms responsible for the targeting of these regulatory factors to specific PM domains requires quantitative information concerning the sites of bulk secretion and endocytosis. Here, we quantitatively characterized the spatial organization of membrane traffic during tip growth by analyzing steady-state distributions and dynamics of FM4-64-labeled lipids and YFP-tagged transmembrane (TM) proteins in tobacco (Nicotiana tabacum) pollen tubes growing normally or treated with Brefeldin A to block secretion. We established that (1) secretion delivers TM proteins and recycled membrane lipids to the same apical PM domain, and (2) FM4-64-labeled lipids, but not the analyzed TM proteins, undergo endocytic recycling within a clearly defined subapical region. We mathematically modeled the steady-state PM distributions of all analyzed markers to better understand differences between them and to support the experimental data. Finally, we mapped subapical F-actin fringe and trans-Golgi network positioning relative to sites of bulk secretion and endocytosis to further characterize functions of these structures in apical membrane traffic. Our results support and further define the classical model of apical membrane traffic at the tip of elongating pollen tubes.
CRIS-Team Scopus Importer:2020-08-14

Structural basis for the shielding function of the dynamic trypanosome variant surface glycoprotein coat - Bartossek, Thomas; Jones, Nicola G.; Schafer, Christin; Cvitkovic, Mislav; Glogger, Marius; Mott, Helen R.; Kuper, Jochen; Brennich, Martha; Carrington, Mark; Smith, Ana-Suncana; Fenz, Susanne; Kisker, Caroline; et al. (Nature Microbiology, 2017)
The most prominent defence of the unicellular parasite Trypanosoma brucei against the host immune system is a dense coat that comprises a variant surface glycoprotein (VSG). Despite the importance of the VSG family, no complete structure of a VSG has been reported. Making use of high-resolution structures of individual VSG domains, we employed small-angle X-ray scattering to elucidate the first two complete VSG structures. The resulting models imply that the linker regions confer great flexibility between domains, which suggests that VSGs can adopt two main conformations to respond to obstacles and changes of protein density, while maintaining a protective barrier at all times. Single-molecule diffusion measurements of VSG in supported lipid bilayers substantiate this possibility, as two freely diffusing populations could be detected. This translates into a highly flexible overall topology of the surface VSG coat, which displays both lateral movement in the plane of the membrane and variation in the overall thickness of the coat.
Keywords: membrane biophysics; membrane trafficking; parasite immune evasion; SAXS